Optimal control applied to vaccination and treatmentstrategies for various epidemiological models - Holly Gaff; Elsa Schaefer (Mathematical Biosciences and Engineering)
Mathematical models provide a powerful tool for investigating thedynamics and control of infectious diseases, but quantifying theunderlying epidemic structure can be challenging especially for newand under-studied diseases.Variations of standard SIR, SIRS, and SEIR epidemiologicalmodels are considered to determine the sensitivity of these models tovarious parameter values that may not be fully known when the models areused to investigate emerging diseases. Optimal control theory is appliedto suggest the most effective mitigationstrategy to minimize the number of individuals who become infected in thecourse of an infection while efficiently balancingvaccination and treatment applied to the models with various costscenarios. The optimal control simulations suggest that regardless of theparticular epidemiological structure and of the comparative cost ofmitigation strategies, vaccination, if available, would be acrucial piece of any intervention plan.